Assessing the Marketability of Locally Produced Chili Paste in Apayao as a Basis for Extension Services of the BSBA Program - Magpia, Jay Kim (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to assess the marketability of locally produced chili paste in Apayao as a basis for BSBA extension services. It was anchored on Consumer Behavior Theory, Sensory Evaluation Theory, Value Chain Theory, and Diffusion of Innovation Theory to explain consumer preferences, product acceptability, and adoption. A descriptive research design combining quantitative and qualitative approaches was employed. Data were collected from 50 respondents, including consumers, farmers, and producers, using a structured questionnaire and sensory evaluation based on a 9-point Hedonic Scale. Descriptive statistics such as frequency, percentage, mean, and standard deviation were used to analyze the data. The findings revealed that respondents were primarily middle-aged, predominantly male, and regularly engaged in cooking. Chili paste was widely consumed daily or several times a week, commonly purchased from local markets, online platforms, and sari-sari stores. The product demonstrated high sensory acceptability across all attributes, with texture receiving the highest rating. Results also indicated strong product acceptability, high purchase intention, and positive perceptions of price and packaging. Consumers showed a high willingness to pay across different product sizes, reflecting strong perceived value. Marketing and distribution preferences emphasized the importance of product labeling, social media promotion, accessibility in local stores, and preference for locally produced products. The study concludes that locally produced chili paste in Apayao has strong market potential and consumer acceptance. It recommends enhancing product development, expanding distribution channels, implementing flexible pricing strategies, and strengthening training and extension services for farmers and producers. The study aligns with SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation and Infrastructure), and SDG 12 (Responsible Consumption and Production) by promoting value-added agricultural products and local enterprise development. It contributes to socio-economic and community sustainability by supporting income generation, local innovation, and inclusive rural development.